Cover Image, Volume 42, Issue 8. Issue 8 (22nd August 2022) - Ding, Yuming; Chen, Chaojia; Ma, Shuaiya; Sheng, Xue; Zhao, Fangcheng; Peng, Jiali; Dong, Haoqing; Ma, Chunhong; Li, Chunyang
Abstract : The cover image is based on the Correspondence Intrinsic PD‐L1 promotes antitumor activity of CD8 + cytotoxic T lymphocytes via in cis interaction with CD80 by Yuming Ding et al., https://doi.org/10.1002/cac2.12337 .